The Neuropsychological Profile of Severe and Enduring Anorexia Nervosa: A Systematic Review - Broomfield, Catherine; Stedal, Kristin; Touyz, Stephen (Frontiers in Psychology, 2021)
Characteristics of Severe and Enduring Anorexia Nervosa (SE-AN) are being investigated to differentiate the patients experiencing SE-AN from those at earlier stages of the AN disease. The current systematic review was the first step in exploring neuropsychological functioning as a potentially identifying characteristic for long-term presentations. With a subgroup of AN patients reflecting a unique neuropsychological profile that is proportionate to the quantity of patients that go on to develop SE-AN, it was the aim of this review to assess neuropsychological functioning in the later stage of the disease. In accordance with PRISMA guidelines, a literature search was conducted using four electronic databases (PsycINFO, MEDLINE, Web of Science, and Scopus) for neuropsychological research on AN participants with a seven or more year illness duration. Datasets that met inclusion criteria were screened for SE-AN participants (N = 166) and neuropsychological data extracted together with potentially confounding variables and information required to conduct a quality assessment. In research investigating decision-making, participants with a SE-AN presentation demonstrated significantly lower functioning compared to healthy controls. There was conflicting evidence for differences in intellectual functioning and set-shifting abilities with no variability indicated in central coherence, memory, attention, reasoning, or processing speed. If findings from this preliminary analysis are confirmed through empirical research, implications include earlier identification of SE-AN patients and more effective treatment development.